Acyl Radical Chemistry via Visible-Light Photoredox Catalysis - Banerjee, Arghya; Lei, Zhen; Ngai, Ming-Yu (Synthesis, 2019)
Visible-light photoredox catalysis enables easy access to acyl radicals under mild reaction conditions. Reactive acyl radicals, generated from various acyl precursors such as aldehydes, α-keto acids, carboxylic acids, anhydrides, acyl thioesters, acyl chlorides, or acyl silanes, can undergo a diverse range of synthetically useful transformations, which were previously difficult or inaccessible. This review summarizes the recent progress on visible-light-driven acyl radical generation using transition-metal photoredox catalysts, metallaphotocatalysts, hypervalent iodine catalysts or organic photocatalysts.1 Introduction2 The Scope of This Review3 Aldehydes as a Source of Acyl Radicals4 α-Keto Acids as a Source of Acyl Radicals5 Carboxylic Acids as a Source of Acyl Radicals6 Anhydrides as a Source of Acyl Radicals7 Acyl Thioesters as a Source of Acyl Radicals8 Acyl Chlorides as a Source of Acyl Radicals9 Acyl Silanes as a Source of Acyl Radicals10 Conclusions and Future Outlook
Keywords: acylation; photoredox catalysis; acyl radicals; visible light; single-electron transfer; oxidation; reduction; cross-coupling